On the optimization of water-energy nexus in shale gas network under price uncertainties. (15th July 2020) - Oke, Doris; Mukherjee, Rajib; Sengupta, Debalina; Majozi, Thokozani; El-Halwagi, Mahmoud
Abstract: This study develops a framework for water-energy nexus optimization in shale gas production and distribution network under uncertainty. Sustainable design of the network is achieved through treatment of wastewater using thermal membrane distillation, whereby a comprehensive design model is integrated within the network to account for energy requirement of the unit. The proposed model also accounts for the problem of scheduling hydraulic fracturing using a continuous time formulation. Various uncertainties are associated with the network. Among different uncertain variables, uncertainties associated with price and demand are crucial as they can affect the optimal configuration significantly. Incorporation of uncertainty in the model seeks to meet the demand of natural gas consumers whilst accounting for the uncertainties associated with the price of final products. Uncertainties are modelled via randomly generated scenarios using beta distribution of the price generated using historical data. The stochastic model is applied to a case study through the maximization of net profit. Three different scenarios are considered for analysis. Results from the three different scenarios show 14.39%, 11.49%, and 12.34% increase in profit respectively as compared to the deterministic approach. Solving all the scenarios together gives an ensemble-average solution with 13.74% increase in expected profit. Savings in the freshwater requirement for fracturing and the energy associated with water management amounted to 23.2% and 42.7%, respectively. Highlights: Robust and profitable operation and design due to incorporation of uncertainties. Uncertainties have profound impact on revenue generation and optimal network. Substantial decrease in water and energy requirements of the network. Profound increase in total profit compared to deterministic approach. Higher revenue obtained is at the expense of additional costs.